Ice lollies: An ice particle generated in supercooled conveyor belts. Issue 10 (24th May 2017) - Keppas, S. Ch.; Crosier, J.; Choularton, T. W.; Bower, K. N.
Abstract: On 21 January 2009, a maturing low‐pressure weather system approached the UK along with several associated frontal systems. As a part of the Aerosol Properties, PRocesses And InfluenceS on the Earth's climate‐Clouds project, an observational research flight took place in southern England, sampling the leading warm front of this system. During the flight, a distinctive hydrometeor type was repeatedly observed which has not been widely reported in previous studies. We refer to the hydrometeors as "drizzle‐rimed columnar ice" or "ice lollies" for short due to their characteristic shape. We discuss the processes that led to their formation using in situ and remote sensing data. Key Points: Ice lollies form when a columnar ice crystal collides with a large water droplet Ice‐lolly formation rates are highest in the Hallett‐Mossop region of cloud Ice‐lolly formation may remove liquid water and increase ice crystal concentrations through secondary particle generation